2002
DOI: 10.1038/sj.gt.3301655
|View full text |Cite
|
Sign up to set email alerts
|

High expression of transgenes mediated by hybrid retroviral vectors in hepatocytes: comparison of promoters from murine retroviruses in vitro and in vivo

Abstract: To achieve high transgene expression in the liverRetroviral vectors are the most commonly used gene transfer vehicles for various cell types. 1 The liver is one of the attractive targets for these vectors, since it synthesizes a myriad of proteins that play pivotal roles in metabolism or hemostasis. 2 One of the major limitations to achieving successful gene therapy in the liver with retroviral vectors is the low level of transgene expression. 3 Although a variety of promoters were examined and used as interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The MSCV retroviral LTR has been shown to drive high expression in hematopoietic and embryonic stem cells 30, 31. The spleen focus‐forming virus LTR induces high levels of expression in hepatocytes and hematopoietic cells 32, 33. Here, we found that this latter LTR used in pFIP/CD promoted higher levels of CD expression in MSCs than did the MSCV‐LTR (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…The MSCV retroviral LTR has been shown to drive high expression in hematopoietic and embryonic stem cells 30, 31. The spleen focus‐forming virus LTR induces high levels of expression in hepatocytes and hematopoietic cells 32, 33. Here, we found that this latter LTR used in pFIP/CD promoted higher levels of CD expression in MSCs than did the MSCV‐LTR (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…30,31 The spleen focus-forming virus LTR induces high levels of expression in hepatocytes and hematopoietic cells. 32,33 Here, we found that this latter LTR used in pFIP/ CD promoted higher levels of CD expression in MSCs than did the MSCV-LTR (Fig. 1c) and 5-FU production was 4.8-fold higher with pFIP/CD than with pMSCV/CD (Fig.…”
Section: Cancer Therapymentioning
confidence: 60%
“…Having previously observed retroviral silencing in over 95% of MoMLV transduced cells, Prasad Alur et al [Alur et al, 2002] recently demonstrated that deleting negatively acting cis elements in the viral LTRs, retaining a permissive primer binding site (PBS) sequence and using the eukaryotic β-glucuronidase promoter could overcome this downregulation in vivo in a mouse model of lysosomal enzyme deficiency. Another study demonstrated that the use of alternative optimised LTR promoters to drive expression form retroviral vectors may avoid severe silencing effects in the liver in vivo [Ohnishi et al, 2002]. Further mechanisms of avoiding the silencing of viral promoters, such as the use of LCRs and MARs, are discussed later.…”
Section: Retroviral Ltr Promotersmentioning
confidence: 99%